Civil rights as determinants of public health and racial and ethnic health equity: Health care, education, employment, and housing in the United States. (April 2018) - Hahn, R.A.; Truman, B.I.; Williams, D.R.
Abstract: This essay examines how civil rights and their implementation have affected and continue to affect the health of racial and ethnic minority populations in the United States. Civil rights are characterized as social determinants of health. A brief review of US history indicates that, particularly for Blacks, Hispanics, and American Indians, the longstanding lack of civil rights is linked with persistent health inequities. Civil rights history since 1950 is explored in four domains—health care, education, employment, and housing. The first three domains show substantial benefits when civil rights are enforced. Discrimination and segregation in housing persist because anti-discrimination civil rights laws have not been well enforced. Enforcement is an essential component for the success of civil rights law. Civil rights and their enforcement may be considered a powerful arena for public health theorizing, research, policy, and action. Highlights: Civil rights are characterized as social determinants of health. Four domains in civil rights history since 1950 are explored in—health care, education, employment, and housing. Health care, education, employment show substantial benefits when civil rights are enforced. Housing shows an overall failure to enforce existing civil rights and persistent discrimination. Civil rights and their enforcement may be considered a powerful arena for public health theorizing, research, policy, and action.